Histone Chaperone Paralogs Have Redundant, Cooperative, and Divergent Functions in Yeast. Issue 4 (1st December 2019) - Savic, Neda; Shortill, Shawn P; Bilenky, Misha; Dobbs, Joseph M; Dilworth, David; Hirst, Martin; Nelson, Christopher J
Abstract: Gene duplications increase organismal robustness by providing freedom for gene divergence or by increasing gene dosage. The yeast histone chaperones Fpr3 and Fpr4 are paralogs that can assemble nucleosomes in vitro ; however, the genomic locations they target and their functional relationship is poorly understood. We refined the yeast synthetic genetic array approach to enable the functional dissection of gene paralogs. Applying this method to Fpr3 and Fpr4 uncovered redundant, cooperative, and divergent functions. While Fpr3 is uniquely involved in chromosome segregation, Fpr3 and Fpr4 cooperate to regulate genes involved in polyphosphate metabolism and ribosome biogenesis. We find that the TRAMP5 RNA exosome is critical for fitness in Δ fpr3 Δ fpr4 yeast and leverage this information to identify an important role for Fpr4 at the 5′ ends of protein coding genes. Additionally, Fpr4 and TRAMP5 negatively regulate RNAs from the nontranscribed spacers of ribosomal DNA. Yeast lacking Fpr3 and Fpr4 exhibit a genome instability phenotype at the ribosomal DNA, which implies that these histone chaperones regulate chromatin structure and DNA access at this location. Taken together. we provide genetic and transcriptomic evidence that Fpr3 and Fpr4 operate separately, cooperatively, and redundantly to regulate a variety of chromatin environments.